2020
DOI: 10.1108/jfm-03-2020-0017
|View full text |Cite
|
Sign up to set email alerts
|

An on-campus university student accommodation model

Abstract: Purpose The purpose of this paper is to develop a model that can be used as a guide for the provision, adaptation and management of on-campus student accommodation spaces and services. Design/methodology/approach A phenomenological research strategy was used for the study. Qualitative data were collected by means of focus group discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Vocational school graduates are taught English specifically based on major. For example, front office majors are taught English with vocabulary [23], [24]. Likewise with students who take majors food and beverage service is taught in the Food and Beverage major Service Area.…”
Section: Resultsmentioning
confidence: 99%
“…Vocational school graduates are taught English specifically based on major. For example, front office majors are taught English with vocabulary [23], [24]. Likewise with students who take majors food and beverage service is taught in the Food and Beverage major Service Area.…”
Section: Resultsmentioning
confidence: 99%
“…Disparities in access to higher education are apparent among Ghanaians from low socioeconomic backgrounds, ethnic minorities (e.g., the Mole-Dagbanis in the Northern region), and women (Anlimachie & Avoada, 2020; Swanzy et al, 2019). Moreover, students who are able to enroll in higher education are met with challenges, such as tuition costs, inadequate educational resources and technology, ineffective instruction, frequent strikes from faculty and staff due to unpaid wages, and lack of adequate residential housing (Sarpong et al, 2022; Simpeh & Shakantu, 2018). The accumulation of these challenges strains students, likely impacting their psychological well-being.…”
Section: Sociocultural and Contextual Factors That Impact Ghanaian Un...mentioning
confidence: 99%
“…Chen and Luo (2014) state that these programs should explicitly state the quality of material and equipment, the acceptance standards of work and tests to be performed. Simpeh and Shakantu (2020) explore quality in terms of functionality of construction facilities. The study reported inadequacies in facilities in higher institutions of learning.…”
Section: Cost Indicatormentioning
confidence: 99%